2014
DOI: 10.1089/vbz.2012.1261
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Surveillance for Informing Pretravel Medical Advice: Imported Malaria in New Zealand 1997–2009

Abstract: Malaria has never been endemic in New Zealand, and all cases have been diagnosed in international travelers. In this paper, we describe malaria cases reported from 1997 to 2009 and discuss epidemiological changes compared to a previous report from 1980 to 1992. From 1997 to 2009, 666 malaria infections were reported, with 410 cases (61.6%) in travelers aged 20-39 and 133 (20%) in military personnel. Infections were caused by Plasmodium vivax in 436 cases (72.7%) and Plasmodium falciparum in 163 (27.2%). In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Any ‘VFR travel’ in conjunction with country of birth and other indicators of ethnicity are likely to provide valuable data on risk groups without data collection issues. Several other studies have supported modifications to routine data collection of notifiable diseases to better understand immigrant health [25, 27, 28]. In Australia, and other countries with low or absent endemic disease, the index case of outbreaks of vaccine preventable diseases such as measles, typhoid and hepatitis A are most likely to be international travellers, and current travel medicine practices need to adapt to target health promotion to high-risk groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any ‘VFR travel’ in conjunction with country of birth and other indicators of ethnicity are likely to provide valuable data on risk groups without data collection issues. Several other studies have supported modifications to routine data collection of notifiable diseases to better understand immigrant health [25, 27, 28]. In Australia, and other countries with low or absent endemic disease, the index case of outbreaks of vaccine preventable diseases such as measles, typhoid and hepatitis A are most likely to be international travellers, and current travel medicine practices need to adapt to target health promotion to high-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…Australian notification data for these vector-borne diseases have not previously been reported by reason for travel, but other developed countries show a high proportion of malaria cases [1, 33, 34] in VFR travellers. While Papua New Guinea and South Asia remain the most common regions of acquisition of imported malaria in Australia [35], the large proportion of cases from sub-Saharan Africa and an increase in Plasmodium falciparum cases as a proportion of total imported malaria in Australia [17] and New Zealand [28] have previously been reported and reflect the changing patterns of migration and travel in the region. Early in the re-emergence of chikungunya in 2004, cases were predominantly returning tourist travellers to islands in the Indian Ocean; however, changes in the global epidemiology of this infection, including large ongoing outbreaks around the globe, has resulted in an expansion of the origins of imported disease to include India and countries in South East Asia [3537], resulting in an increased risk for VFR travellers [38] of ethnicities common in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Africa (most commonly Sudan, Uganda and Nigeria) was an important source of imported cases, likely reflecting increased immigration from this region, 51 with infections detected both on arrival and following VFR travel. 60 VFR travellers tend to be less inclined to seek, and less successful in adhering to, mosquito avoidance measures and malaria chemoprophylaxis compared with other traveller groups, 61 , 62 thereby increasing infection risk. Most P. falciparum, P. ovale and P. malariae cases in our study were acquired in Africa, consistent with global species distribution.…”
Section: Discussionmentioning
confidence: 99%
“…A study from New Zealand, which has a similar traveller profile to Australia, demonstrated that PNG and the Western Pacific accounted for the majority of imported malaria cases (39%), with Africa accounting for 21%. 60 …”
Section: Discussionmentioning
confidence: 99%